2016
DOI: 10.1080/1744666x.2016.1178574
|View full text |Cite
|
Sign up to set email alerts
|

The role of proton pump inhibitor therapy in the management of eosinophilic esophagitis

Abstract: Eosinophilic esophagitis (EoE) is a chronic esophageal disease characterized by a Th2 inflammatory response triggered by food/environmental allergens. Solid data confirm that up to half of patients with suspected EoE achieve complete remission on proton pump inhibitors (PPI) therapy. This disease phenotype is currently labelled as PPI-responsive esophageal eosinophilia (PPI-REE). Albeit initially believed to represent gastro-esophageal reflux disease (GERD), evolving evidence has underscored that PPI-REE and E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…There is still controversy surrounding the entity and extent to which it overlaps with or is a subtype of EoE. 20,21 Clinically, a number of conditions can cause esophageal eosinophilia. However, when patients present with typical symptoms of esophageal dysfunction, atopy, endoscopic findings suggestive of EoE and biopsy specimens with marked esophageal eosinophilia, they appear to have EoE.…”
Section: Relationship Between Eoe and Other Forms Of Esophagitis Withmentioning
confidence: 99%
“…There is still controversy surrounding the entity and extent to which it overlaps with or is a subtype of EoE. 20,21 Clinically, a number of conditions can cause esophageal eosinophilia. However, when patients present with typical symptoms of esophageal dysfunction, atopy, endoscopic findings suggestive of EoE and biopsy specimens with marked esophageal eosinophilia, they appear to have EoE.…”
Section: Relationship Between Eoe and Other Forms Of Esophagitis Withmentioning
confidence: 99%
“…This category is being increasingly recognized in the medical community as a group of patients with overlapping features of GERD and EoE. 2,20,21 A prospective study of patients within this clinical category would be necessary to establish whether ALOX15 IHC could be used to predict the likelihood of that patient to respond favorably to antireflux therapy or to antigen elimination/topical steroids treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Since these cases were clinically classified as GERD based on their response to therapy with PPI and the lack of sufficient eosinophilia in their esophageal biopsies, it is likely that they belong to the so-called group of “PPI responsive esophageal eosinophilia.” This category is being increasingly recognized in the medical community as a group of patients with overlapping features of GERD and EoE. 2,20,21 A prospective study of patients within this clinical category would be necessary to establish whether ALOX15 IHC could be used to predict the likelihood of that patient to respond favorably to antireflux therapy or to antigen elimination/topical steroids treatment.…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis of 33 studies, comprising 619 patients with symptomatic esophageal eosinophilia, demonstrated that PPI therapy induced clinical response and histologic remission in 60.8% and 50.5% of patients, respectively [91]. On PPI maintenance, sustained remission has been observed in 73-86% of pediatric and adult PPI-REE patients [92]. Low-dose PPI maintenance with esomeprazole at 1 mg/kg (maximum of 40 mg) daily dosing in 57 EoE children, who responded initially to an 8-week esomeprazole trial at 1 mg/kg dose (maximum of 40 mg) twice daily, achieved clinical response in 86% and histologic remission in 70.1% of these children at 1 year with an adequate safety profile [93].…”
Section: Treatment Of Eoementioning
confidence: 99%